Remarkable Modulation of Self‐Assembly in Short γ‐Peptides by Neighboring Ions and Orthogonal H‐Bonding. Issue 43 (11th July 2017) - Jadhav, Sandip V.; Amabili, Paolo; Stammler, Hans‐Georg; Sewald, Norbert
Abstract: Gabapentin, an antiepileptic drug, is known to form stable helical structures in short peptides. Distinctly, we report on the newly synthesized γ‐analogue of gabapentin, that is, γ‐gabapentin (γ‐Gpn), which manifests β‐sheet character at molecular and nanofibrous hydrogels at the supramolecular level. We investigated the influence of proximally immobilized cationic amino acids (lysine and arginine) on the self‐assembly of backbone‐expanded tripeptide motif. Interestingly, arginine was found to be superior, both physically and mechanically, over lysine in driving hydrogelation. We have concluded that intrinsic and biochemically distinct properties of the guanidinium ion of arginine (compared to ammonium ion of lysine) have contributed towards this effect. Furthermore, similar to pyroglutamyl (pGlu) modified amyloid β peptides, N ‐pGlu modification of our self‐assembling tripeptide motif exerts a dramatic influence on aggregation and exhibits enhanced β‐sheet character, accelerated self‐assembly kinetics, improved optical transparency and provides higher mechanical stiffness to the peptide hydrogel. Abstract : Bio(stable)material : The bottom‐up design and systematic modulation of material properties of hydrogels obtained from a short γ‐peptide foldamer are discussed. On account of its intrinsically distinct biochemical properties, arginine demonstrates a favorable influence on the hydrogel material over lysine. Similar to amyloid β, the impact of N ‐pyroglutamyl modification on the aggregation of short γ‐peptides motif is investigated. Such modification imparts dramatic stiffness into the hydrogel.